A climate policy revolution : what the science of complexity reveals about saving our planet - Kupers, Roland, 1959- (Harvard University Press, 2020)
"In this book, Roland Kupers argues that the climate crisis is well suited to the bottom-up, rapid, and revolutionary change complexity science theorizes; he succinctly makes the case that complexity science promises policy solutions to address climate change"--